Pengaruh Work Life Balance dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT PLN ULP di Banjarbaru - Prila Geonestri Pramanda; Lamsah Lamsah; Dewi Ariefahnoor (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the effect of Work Life Balance (WLB) and Job Satisfaction (JS) on employee performance at PT PLN ULP Banjarbaru, both jointly and individually, while also identifying the most dominant factor influencing performance. The research background is based on theoretical frameworks, expert opinions, and the researcher’s direct observations of workplace conditions. To achieve the research objectives, hypotheses were formulated and tested using empirical data. The study employed a quantitative approach with a saturated sampling technique, involving the entire employee population. A total of 37 respondents participated as the research sample. The collected data underwent validity and reliability testing to ensure the accuracy and consistency of the measurement instruments. Furthermore, classical assumption tests were performed to meet the requirements of multiple linear regression analysis. The results of the analysis demonstrate that both Work Life Balance and Job Satisfaction have a significant effect on employee performance, both simultaneously and partially. Among the two independent variables, Work Life Balance was identified as the most dominant factor influencing performance, indicating that employees who maintain a better balance between their personal and professional lives tend to perform better in their work. The adjusted R² value of 0.862 signifies that 86.2% of the variation in employee performance can be explained by the two independent variables studied, while the remaining 13.8% is influenced by other variables not included in this research model, such as leadership style, work motivation, or organizational culture. These findings highlight the importance of maintaining a healthy work-life balance and ensuring job satisfaction to optimize employee performance. The study suggests that organizations should implement policies and practices that promote flexibility, support employee well-being, and foster a positive work environment to enhance both individual and organizational outcomes.